A large-scale trial in Chennai, India shows effective reduction of Anopheles stephensi populations by the biolarvicide Natular - Candasamy Sadanandane; Ananganallur Nagarajan Shriram; Ashwani Kumar; Mariapillai Kalimuthu; Ranganathan Krishnamoorthi; S. Selvakumar; Annamalai Sakthivel; Manju Rahi (PLoS ONE, 2025)
Biolarvicides present an environmentally safer alternative to chemical larvicides, demonstrating selectivity against target species. However, the available options for biolarvicide use in mosquito control remain limited. This study aimed to assess the effectiveness of three formulations of the biolarvicide Natular, namely the 20.6% Emulsifiable Concentrate (EC), 2.5% G30 granular, and 7.48% tablet (DT) for direct application, against Anopheles stephensi in large-scale field trials conducted in Chennai, India. When the 7.48% DT formulation was applied at a rate of 1 tablet per 200 L in overhead tanks with An. stephensi breeding sites, on an average, led to a > 90–100% reduction in An. stephensi larval and pupal density for a duration of 8–9 weeks in rainy, winter and summer seasons. Similarly, the 2.5% G30 formulation, at a concentration of 0.074 mg (AI)/L in overhead tanks, impressively suppressed An. stephensi larval and pupal density by 91–100% for 4–5 weeks in three seasons. The application of the 20.6% EC formulation at 0.073 mg (AI)/L in overhead tanks achieved a remarkable 100% reduction in larval and pupal density for 2 weeks in all seasons. The Natular 7.48% DT formulation is well-suited for An. stephensi larval control at 1 tablet per 200 L with an 8-week application interval. The 2.5% G30 formulation is recommended at 0.074 mg (AI)/L at 4-week intervals. Meanwhile, the 20.6% EC formulation can effectively control An. stephensi at 0.073 mg (AI)/L with fortnightly application intervals. These Natular formulations serve as potent biolarvicides, offering a valuable tool for An. stephensi control within the Integrated Vector Management (IVM) program.